1994
DOI: 10.1007/bf02235421
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of nitrate and ammonium uptake by the natural populations of marine phytoplankton in the surface water of the Oyashio region during spring and summer

Abstract: Figure Legends

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…5). Previous authors have observed a similar trend (Shiomoto et al 1994), although not to the extent shown here. This low rate during winter may, like the ammonium uptake, be influenced by temperature.…”
Section: Ammonium and Nitrate Uptake By Mpbsupporting
confidence: 84%
See 2 more Smart Citations
“…5). Previous authors have observed a similar trend (Shiomoto et al 1994), although not to the extent shown here. This low rate during winter may, like the ammonium uptake, be influenced by temperature.…”
Section: Ammonium and Nitrate Uptake By Mpbsupporting
confidence: 84%
“…The ammonium uptake rates in winter and summer fitted very different kinetic curves (Fig. 5) values observed for phytoplankton (Wheeler et al 1982, Shiomoto et al 1994, Collos et al 2005, they differed by one order of magnitude between seasons (Table 2), suggesting external regulation of uptake. Changes in uptake rates may result from regulatory response mechanisms controlled by physiological or ecological factors related to substrate conditions, irradiance, day length, temperature and community structure (Eppley et al 1969, Berges et al 2002, reviewed in Collos et al 2005).…”
Section: Ammonium and Nitrate Uptake By Mpbmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, only selected data from the original studies were included in this compilation, with an apparent bias towards selecting high values of K NO 3 . For example, the greatest value in the compilation was the only one selected from several presented by Shiomoto et al (1994), even though the validity of that particular value was specifically questioned by Shiomoto et al (1994). One could therefore question whether the relationship presented by Collos et al (2005) truly represents the response of phytoplankton to nitrate concentrations in the ocean.…”
Section: Methodsmentioning
confidence: 99%
“…Typical values of the half saturation constant for growth (Ks) nitrate for natural phytoplankton populations have been reported to be ϳ1.5 mol L Ϫ1 in coastal waters (Fisher et al 1988) and Ͻ0.6 mol L Ϫ1 in the Oyashio Region (off Japan; Shiomoto et al 1994). However, high DFe concentrations in the dust treatment might have increased the nitrate uptake capacity: the amount of DFe provided by the 0.25 mg L Ϫ1 dust addition was 0.74 nmol L Ϫ1 (on average over the incubation period) and resulted in a total DFe of 1.64 nmol L Ϫ1 .…”
mentioning
confidence: 99%